KIRSTEN WELD, Paper Cadavers: The Archives of Dictatorship in Guatemala: Queen’s University Archives, Kingston, Ontario - Home, Heather (Archivaria, 2015)
Paper Cadavers: The Archives of Dictatorship in Guatemala. KIRSTEN WELD. Durham, NC: Duke University Press, 2014. xvi, 335 pp. ISBN 978-0-8223-5597-7.